The main difficulties encountered by primipara and multipara women in breastfeeding with exclusive breastfeeding (Research, Society and Development, 2023)
Exclusive breastfeeding is a fundamental factor for the nutritional, motor, cognitive and psychosocial progress of infants, especially in the first months of life. Therefore, its technique must be taught, since the lack of information about it and the correct positioning and attachment by mothers has been one of the main reasons for them to stop breastfeeding exclusively, before the recommended time, happening early weaning. The objectives of this work are to understand the main problems faced by primiparous and multiparous women over time of exclusive breastfeeding. This is a study with a quantitative, descriptive and cross-sectional approach. This study was carried out from the application and analysis of data collected in a questionnaire directed to primiparous and multiparous women about the main adversities encountered in exclusive breastfeeding. Thus, it is expected that this study will shed light on the relevance of guidance, and the assistance of health professionals, who, together with the support of family, friends and the booklet developed, will help during breastfeeding, minimizing the difficulties.